2014
DOI: 10.1590/1678-775720130052
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the addition of iodoform on the physicochemical properties of an epoxy-based endodontic sealer

Abstract: Due to the low radiopacity of Sealer 26, iodoform is frequently empirically added to this sealer. Thus, the interference of this procedure with the physicochemical properties of Sealer 26 must be evaluated.Objective This study evaluated the influence of the addition of iodoform on setting time, flow, solubility, pH, and calcium release of an epoxy-based sealer. Material and Methods The control group was pure Sealer 26, and the experimental groups were Sealer 26 added with 1.1 g, 0.55 g or 0.275 g of iodoform. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…These substances could negatively influence the other properties of the sealers. 25 The present study suggested that when radio-opacity was evaluated by the simulator method, the same sealer that was considered only slightly radio-opaque by the birpublications.org/dmfr Dentomaxillofac Radiol, 44, 20140422…”
Section: Discussionmentioning
confidence: 78%
“…These substances could negatively influence the other properties of the sealers. 25 The present study suggested that when radio-opacity was evaluated by the simulator method, the same sealer that was considered only slightly radio-opaque by the birpublications.org/dmfr Dentomaxillofac Radiol, 44, 20140422…”
Section: Discussionmentioning
confidence: 78%
“…18,19 In contrast, the final setting of the epoxy resin-based sealer had been achieved by 7 days. 19,21 The concept that "like dissolves like" (polar solvents are better at dissolving polar substances), and vice versa explains the higher incidence of remaining sealer residues for the cleaning protocol employing ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these sealers require a long time to achieve final setting, and it is not clear at which time-point it is optimal to perform acid etching. 18,19 Therefore, the aim of this study was to evaluate the effect of acid etching on the dentin surface, performed either immediately or 7 days after removal of the endodontic sealer with solvents.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…However, few studies have examined the viscosity of root canal sealers. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 The majority of previous studies measuring the flowabilities of root canal sealers 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 used the simple press method that is specified by the International Organization for Standardization (ISO) 6876. 20 Although this method is simple and economical, 18 the information obtained is limited in that this method can determine only the compressed sealer diameter.…”
Section: Introductionmentioning
confidence: 99%